Pemecahan masalah kontekstual: sebuah analisis diferensiasi berdasarkan kemampuan awal matematika siswa - Napfiah, Siti; Katupu, Paulus; Purnomo, Heri (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to analyze and precisely describe the profile of students' contextual problem-solving skills differentiated by their initial mathematical proficiency levels. Design/methodology/approach: This descriptive qualitative study involved two purposefully selected students (one with high and one with low mathematical ability). Data were systematically gathered utilizing written diagnostic tests and in-depth interviews, structured around four fundamental problem-solving indicators. Findings: Both subjects successfully satisfied the four basic problem-solving indicators. Nevertheless, the high-ability student exhibited superior cognitive mastery, evidenced by significantly clearer articulated resolution strategies and meticulous mathematical justifications in both test responses and interviews compared to the low-ability peer. Practical implications: These findings compel mathematics educators to operationalize differentiated instructional strategies, systematically tailoring pedagogical interventions to students' baseline proficiencies to optimally cultivate their contextual problem-solving capabilities. Originality/value: This research provides a microscopic perspective into the qualitative disparities in cognitive articulation and procedural detail between students of varying abilities, particularly highlighting nuances that persist even when baseline problem-solving metrics are ostensibly met.   Purpose: Penelitian ini bertujuan untuk menganalisis dan mendeskripsikan secara spesifik profil kemampuan pemecahan masalah kontekstual siswa berdasarkan perbedaan tingkat kemampuan awal matematika. Design/methodology/approach: Studi kualitatif ini melibatkan dua siswa (satu berkemampuan matematika tinggi dan satu rendah) sebagai subjek penelitian. Data dikumpulkan melalui instrumen tes tertulis dan wawancara mendalam yang dievaluasi menggunakan empat indikator pemecahan masalah. Findings: Kedua subjek pada dasarnya mampu memenuhi keempat indikator pemecahan masalah. Namun, subjek berkemampuan tinggi menunjukkan tingkat penguasaan yang lebih superior, ditandai dengan artikulasi strategi dan justifikasi matematis yang jauh lebih jelas dan terperinci pada hasil tes maupun wawancara dibandingkan subjek berkemampuan rendah. Practical implications: Temuan ini mendorong guru matematika untuk merancang strategi pembelajaran berdiferensiasi yang menyesuaikan intervensi pedagogis dengan profil kemampuan awal siswa untuk mengoptimalkan keterampilan pemecahan masalah kontekstual secara individu. Originality/value: Kajian ini memberikan wawasan mikroskopis mengenai kesenjangan kualitas artikulasi dan detail proses kognitif antara siswa dengan kemampuan berbeda, meskipun keduanya secara teknis mencapai ambang batas indikator dasar pemecahan masalah.